A Novel Anti-Atherogenic Role for COX-2 - Potential Mechanism for the Cardiovascular Side Effects of COX-2 Inhibitors - Narasimha, Ajay (2007)
Atherosclerosis, the underlying cause of cardiovascular disease, is characterized by lipid accumulation, lipoprotein oxidation, and inflammation. Products of the cyclooxygenase (COX) pathway participate in acute and chronic inflammation. The inducible form of COX, COX-2, generates lipid mediators of inflammation that are pro-inflammatory and COX-2-selective inhibitors are potent anti-inflammatory agents. However, clinical data suggest an increased risk of cardiovascular side effects in patients using COX-2-selective inhibitors. In this paper, we sought to determine the affect of COX-2 deficiency on atherosclerosis-related lipoprotein metabolism in mice. We demonstrate that COX-2 deficiency resulted in i) accumulation of lipids in circulation and liver, ii) pro-inflammatory properties of HDL as measured by HDL’s increased reactive oxygen species (ROS) content, decreased paraoxonase 1 (PON1) activity, decreased serum apoA-1, reduced ability to efflux cholesterol and to prevent LDL oxidizability, and iii) increased TXB(2) in circulation. Moreover, when placed on an atherogenic diet, COX-2 deficiency resulted in i) increased lipid deposition in the aorta, ii) a further dramatic imbalance in circulating eicosanoids, i.e. decreased serum PGI(2) coupled with increased PGE(2) and TXB(2), and iii) a marked elevation of pro-inflammatory cytokines, TNF and IL-6. Our results suggest, for the first time, that COX-2 deficiency contributes to the pro-atherogenic properties of HDL in mice.